Medium and Low Voltage Quality Improvement with Shunt Bank Capacitor and Transformer Tap on Morocco Tapung Feeder Duri - Sepannur Bandri; Liliana Liliana; Rafika Andari; Zuriman Anthony (Universitas Islam Raden Rahmat, Malang, 2025)
Voltage and frequency quality are paramount in 20 kV distribution systems that supply both medium and low voltage feeders. This study explores the significant voltage deficiency in the Maroko Tapung extension of PT PLN (PERSERO), ULP Duri, which dropped 16% from the nominal value. The main objective is to implement a comprehensive voltage restoration strategy to improve the efficiency of the 20 kV distribution system so that it reaches a better standard. The restoration was carried out by setting tap changers, installing shunt capacitor banks, and gradually increasing the tap settings on distribution transformers. Simulation results show a significant improvement in the minimum voltage level across the network, with the lowest voltage on the medium voltage side increasing to 91.69% and on the low voltage side to 90.47%. These outcomes demonstrate that the implemented multi-stage restoration procedures effectively brought the voltage quality within the acceptable limits defined by SPLN 1: 1987 standards, which permit a deviation of +5% and -10% from the nominal voltage. This study highlights the effectiveness of combined tap adjustments and shunt capacitor installation in mitigating voltage drops and ensuring compliance with regulatory standards in distribution systems.